Promoting beliefs in the inalienability of human rights by attributing uniquely human emotions through multiple categorization. Issue 3 (4th May 2018) - Albarello, Flavia; Crisp, Richard; Rubini, Monica
ABSTRACT: The combination of multiple categorization (i.e., the use of multiple criteria to define others) and human identity—the superordinate group of human beings—has recently been highlighted as a method to reduce implicit (i.e., attribution of secondary emotions) and explicit (i.e., attribution of human rights) dehumanization toward Blacks. In two studies aimed to replicate such evidence the mediating role of secondary emotions in explaining the impact of multiple and human categorization in reducing dehumanization was assessed. The role of implicit cognition, such as attribution of secondary emotions in leading people to attribute human rights to minorities, is discussed.